2016
DOI: 10.1016/j.ijthermalsci.2016.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flow and heat transfer characteristics of interrupted microchannel heat sink with ribs in the transverse microchambers

Abstract: The paper is focused on the investigation of the laminar flow and heat transfer characteristics in the interrupted microchannel heat sink with ribs in the transverse microchambers. A three-dimensional model based on finite volume approach and SIMPLEC algorithm is performed considering entrance effect, conjugate heat transfer, viscous heating and temperature-dependent thermo-physical properties. Five different rib configurations are considered, including rectangular, backward triangular, diamond, forward triang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 19 publications
4
38
0
Order By: Relevance
“…The reasons were: 1) the cooling area doubled because the bumps on both the top and bottom substrates were connected together when b/c > 1.0; 2) the asymmetrical pair-vortex due to the asymmetrical geometry played a special role, i.e., Figure 9 shows the preferential value was about b/c = 1.25. The reasons were: (1) the cooling area doubled because the bumps on both the top and bottom substrates were connected together when b/c > 1.0; (2) the asymmetrical pair-vortex due to the asymmetrical geometry played a special role, i.e., the larger vortex in the pair-vortex could compel the smaller one to the center ( Figure 10c); (3) the connected bumps (near the top side of a trapezoidal bump, Figure 10b,c) acted as the wall of the microchannel in the MCHS, and the fluids in other regions (fore and rear rake of the trapezoid, Figure 10a,d) were interconnected, as described in Chai et al [11]; and (4) conversely, the greater the bump width, the greater the pressure drop, and subsequently, the greater the pump power. In a word, 1.0 < b/c < 1.25 was the range of preferential values.…”
Section: Effect Of the Bump Widthmentioning
confidence: 86%
See 2 more Smart Citations
“…The reasons were: 1) the cooling area doubled because the bumps on both the top and bottom substrates were connected together when b/c > 1.0; 2) the asymmetrical pair-vortex due to the asymmetrical geometry played a special role, i.e., Figure 9 shows the preferential value was about b/c = 1.25. The reasons were: (1) the cooling area doubled because the bumps on both the top and bottom substrates were connected together when b/c > 1.0; (2) the asymmetrical pair-vortex due to the asymmetrical geometry played a special role, i.e., the larger vortex in the pair-vortex could compel the smaller one to the center ( Figure 10c); (3) the connected bumps (near the top side of a trapezoidal bump, Figure 10b,c) acted as the wall of the microchannel in the MCHS, and the fluids in other regions (fore and rear rake of the trapezoid, Figure 10a,d) were interconnected, as described in Chai et al [11]; and (4) conversely, the greater the bump width, the greater the pressure drop, and subsequently, the greater the pump power. In a word, 1.0 < b/c < 1.25 was the range of preferential values.…”
Section: Effect Of the Bump Widthmentioning
confidence: 86%
“…the larger vortex in the pair-vortex could compel the smaller one to the center ( Figure 10c); 3) the connected bumps (near the top side of a trapezoidal bump, Figure 10b,c) acted as the wall of the microchannel in the MCHS, and the fluids in other regions (fore and rear rake of the trapezoid, Figure 10a,d) were interconnected, as described in Chai et al [11]; and 4) conversely, the greater the bump width, the greater the pressure drop, and subsequently, the greater the pump power. In a word, 1.0 < b/c < 1.25 was the range of preferential values.…”
Section: Effect Of the Bump Widthmentioning
confidence: 90%
See 1 more Smart Citation
“…On top of that, flow disruption in a wavy channel promotes vortex creation which aids in coolant mixing and subsequently enhances the microchannel heat sink performance. Besides, Chai et al have conducted a series of numerical analysis to investigate the flow and heat transfer characteristics of an interrupted microchannel heat sink by installing different configurations of ribs in the transverse microchambers [9]. Based on the simulation results obtained, it is demonstrated that the heat transfer performance of an interrupted micro-channel heat sink is comparatively greater than that of a straight-channel heat sink owing to the enhanced heat transfer coefficient through fluid mixing and re-initialization of the thermal boundary layer in the microchannel heat sink.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further enhance the cooling ability of the currently available mini/microchannel heat sinks, researchers have investigated the cooling system configuration [3,4,5], working fluids [6,7,8] and other relevant parameters [9][10][11][12]. Among these methods, the mini/microchannel heat sink with N/MPCS as working fluid has attracted the researchers' attentions, because it combines the advantages of both mini/microchannel and N/MPCS.…”
mentioning
confidence: 99%